Design of a real–time water quality monitoring and control system using Internet of Things (IoT). Issue 1 (31st December 2022) - Chafa, Allen T.; Chirinda, Gibson P.; Matope, Stephen
Abstract: United Nations (UN) sustainable development goal 6 focuses on clean water and sanitation for all. To date, one-third of the world's population lack access to clean, safe water. The traditional water purification methods cannot monitor and control water quality parameters from the early stages. In this paper, Internet of Things (IoT) is used to develop a real-time water quality monitoring and control system for a water treatment plant. A microcontroller is developed and interfaced with sensors to detect any deviations in the water quality parameters from the World Health Organization (WHO) standards. Every stage of the water treatment process is tested for quality, and deviations from the WHO standard triggers an autonomous control measure. A simulation model and a working prototype are developed. The research produces the expected results: accurate monitoring and control of water parameters.